The Arabidopsis small G‐protein AtRAN1 is a positive regulator in chitin‐induced stomatal closure and disease resistance - Song, Zhiqiang (Mol Plant Pathol, 2020)
Chitin, a fungal microbial‐associated molecular pattern, triggers various defence responses in several plant systems. Although it induces stomatal closure, the molecular mechanisms of its interactions with guard cell signalling pathways are unclear. Based on screening of public microarray data obtained from the ATH1 Affymetrix and Arabidopsis eFP browser, we isolated a cDNA encoding a Ras‐related nuclear protein 1 AtRAN1. AtRAN1 expression was enriched in guard cells in a manner consistent with involvement in the control of the stomatal movement. AtRAN1 mutation impaired chitin‐induced stomatal closure and accumulation of reactive oxygen species and nitric oxide in guard cells. In addition, Atran1 mutant plants exhibited compromised chitin‐enhanced plant resistance to both bacterial and fungal pathogens due to changes in defence‐related genes. Furthermore, Atran1 mutant plants were hypersensitive to drought stress compared to Col‐0 plants, and had lower levels of stress‐responsive genes. These data demonstrate a previously uncharacterized signalling role for AtRAN1, mediating chitin‐induced signalling.